Effect of extraction time and temperature on total flavanoid contents of petai belalang (leucaena leucocephala) seed pretreated by enzymatic hydrolysis - Nor Hanimah, Hamidi; Nurul Athirah, Mohd Alwi; Tarmalingam, Haishwari; Siti Sabirah Ani, Kutty; Siti Nur Nadzmiah, Mohd Nor (Universiti Putra Malaysia, 2021)
The abundant availability of Leucaena leucocephala (petai belalang) in Malaysia was one of the contributing factors of this research. The phytochemicals obtained from this plant will contribute towards many fields mainly medicine and it becomes more favorable as compared to the modern medicines used these days. Diseases such as cancer, high blood pressure and diabetes are very crucial, and it occurs frequently among all ages of citizens in Malaysia. Therefore, phytochemicals in this plant can be a great substitute of modern medicines. However, lignin is known to interfere with the cell wall polysaccharides digestion, and hence considered as an anti-quality component in forages. To improve phytochemicals extraction, an effective degradation method of lignin is in demand. Thus, the goal of the present study was to investigate the feasibility of using enzymatic hydrolysis by laccase from Trametes versicolor (LTV) to breakdown lignin using mild reaction condition. To clarify the effect of enzymatic hydrolysis, a preliminary study on the percentage of lignin removal was conducted that taking the effect of LTV concentration, incubation temperature and time into consideration. The results were then used to analyze total flavonoid contents (TFC) of L.leucocephala seed after the extraction by using microwave-assisted hydrodistillation (MAHD) method. In view of this, extraction temperature and time were varied. TFC was estimated by UV-VIS spectrophotometer for quantification by using quercetin as standard. The result emerge from this study showed that the TFC was high in the extraction temperature of 60˚C in 12 min with an average of 1639 mgQE/g.d.w and the lowest TFC was recorded at 30˚C with 677 mgQE/g.d.w. Further analysis showed that enzymatic hydrolysis has assisted the extraction of flavonoids, thus, provided scientific method to extract flavonoid as an alternative therapy for various diseases.